Correlation between preoperative imaging parameters and postoperative basic kinematics-based functional outcome in patients with tibial plateau fractures. (May 2019) - Warschawski, Yaniv; Drexler, Michael; Batko, Brian; Elias, Shlomo; Goldstein, Yariv; Frenkel Rutenberg, Tal; Schermann, Haggai; Steinberg, Ely L.
Abstract: Background: Functional scores and radiographs are often used to assess function and predict development of osteoarthritis in patients with multi-fragmentary tibial plateau fractures (TPFs). Locomotion, which is the primary goal of fracture treatment, is rarely assessed. The objective of this study was to assess functional ability of patients after TPF fixation using spatio-temporal gait analysis (STGA), and to compare STGA variables with self-reported functional scores and preoperative fracture characteristics. Methods: Preoperative CT scans of 21 patients with complete articular multi-fragmentary TPFs were evaluated for number of fragments, maximum gap between the fragments and maximum articular depression. All patients underwent STGA (velocity, cadence, step length of the affected and the unaffected leg, single-limb support by the affected and the unaffected leg, and double-leg support) and filled the Knee Society Score and the Short Form-12 questionnaires on average 3 years (SD = 1.56, range, 2–5.8) post-injury. Findings: Step length and single-limb support time of the affected leg were shorter compared to the unaffected leg ( p  = 0.02 and p  = 0.007, respectively). Number of fracture fragments correlated with cadence ( R  = −0.461, p  = 0.04) and velocity ( R  = −0.447, p  = 0.04). Interpretation: Given that both higher fracture comminution and deformity on the one hand and the above gait parameter alterations on the other hand are associated with knee osteoarthritis, STGA may be used for routine postoperative evaluation of patients after TPF fixation. Highlights: Tibial plateau fractures are associated with accelerated knee joint degeneration. The study investigates correlation between fracture characteristics and gait parameters. Higher number of fracture fragments negatively correlates with velocity and cadence. Affected limbs had shorter step length and single-limb support times.